Assessing the impact of laptop integration on students' self-confidence and self-efficacy in technology use: the case of middle school students in Abu Dhabi - Alshehhi, Hanan; Sandoval-Hernández, Andrés; Eryilmaz, Nurullah (Frontiers in Education, 2025)
This study examines the quantitative effects of a laptop introduction program in Abu Dhabi's middle schools on students' self-confidence and self-efficacy in using technology. The quantitative phase involved 198 students, with data collected pre- and post-intervention through a survey questionnaire. The study employed a control and intervention group design, allowing for comparative analysis. Using statistical models, the study explored the impact of facilitating conditions, social influence, experience, socio-economic status, and gender on students' self-confidence and self-efficacy. Results indicated a significant positive relationship between gender and self-confidence, with male students reporting higher self-confidence in technology use. Facilitating conditions, such as access to various technological devices, were also positively associated with self-confidence, while prior experience emerged as the sole significant predictor of self-efficacy. By situating the study in the under-researched context of Abu Dhabi, this research addresses the gap in evidence from Middle Eastern education systems and highlights how contextual factors shape the outcomes of technology integration. The findings contribute to international debates on digital inclusion by showing that successful laptop integration depends not only on access to devices but also on students' prior experience and home resources, offering practical insights for policymakers and educators seeking to foster equitable digital learning environments.